Frequency of COVID-19 Infection in Patients with Sudden Loss of Smell (Bangladesh Journal of Otorhinolaryngology, 2021)
Background: The novel human corona virus disease (COVID-19) is the fifth documented pandemic in history since the 1918 flu pandemic. Along with other clinical features, loss of smell has been reported as a prime symptom in COVID-19 positive patients. The aim is to determine the frequency of COVID-19 infection in patients who came with a history of the sudden development of loss of smell.Materials & Methods: This study was done in Uttara Crescent Hospital, a private hospital in Dhaka, Bangladesh. Data were collected retrospectively from hospital records in between 01 April 2020 and 30 November 2020, total 48 patients were included in this series. All the patients came with history of fever, sore throat, cough, loss of smell and altered taste, proper history were taken and examined. The patient with suspected COVID-19 infection was sent for RT-PCR testing. About 24 patients were included in the study with the history of loss of smell with or without other symptoms from the recorded data.Results: Among the 48 patients male were 34 and female 14. The age of the patients was in between 13 and 64 years. COVID-19 infection was confirmed in 34 patients (70.83%) in RTPCR testing.Conclusion: Loss of smell is a significant symptom of COVID-19 infection, along with other symptoms. In the current study, the prevalence of COVID-19 infection is 70.83% in patients with history of sudden loss of smell. It does not reflect the country’s actual picture because of a minimal number of study populations. Further study is needed find out prevalence in Bangladesh.Bangladesh J Otorhinolaryngol 2021; 27(2): 152-158